Legal Accountability of Recording Transparency in Village Fund Financial Reporting - Atrya - Yusnidhar; Harun Harun; Aidul Fitriciada Azhari (Muhammadiyah University Press, 2021)
Objective: This article aims to find out the legal accountability of recording transparency in village fund reporting, especially in Gatak Village and Krecek Village, Delanggu District, Klaten Regency, knowing what obstacles are hamper to realizing transparency in recording and reporting village funds.Method: This type of research is empirical or sociological research. Empirical research is a type of research that is used to solve problems by examining secondary data first and then proceeding with conducting primary data research in the field and the application of law in society. The writing method used in this research is descriptive research. Findings: Transparency of Recording and Reporting of Village Funds of Gatak and Krecek Villages, to realize good governance, this has been proven by the accountability reports and the results of interviews that have been carried out by the authors in accordance with existing mechanisms based on Law No. 6 of 2014 concerning Villages, and Minister of Home Affairs number 113 of 2014. About Guidelines for Regional Financial Management. From the interviews, it was found that there were weaknesses in terms of delays in funds coming down from the center, and this would also result in a delay in activities along with existing recording and reporting, in addition to the lack of maximizing technology resources in order to fulfill transparency to the public of existing human resources, but these obstacles are still able to be resolved and do not interfere with the performance of the village government for the better.Purpose: This research is expected to be able to contribute ideas in the development of legal science, especially state administrative law, especially regarding the implementation of good governance at the village level. This research can know the recording and reporting mechanisms to achieve transparency in village fund financial reporting, and can provide the views of readers and writers who have problems with similar problems, also determine the author’s ability to apply the knowledge that has been obtained.Novelty: Different from previous research, this paper has differences that emphasize more on the role of village officials in legal responsibility in the transparency of recording and reporting village funds.